Pengaruh Pemberian Ekstrak Kunyit Putih (Curcuma zedoaria Rocs.) terhadap Aktivitas Superoksida Dismutase (SOD) - Udayani, Ni Nyoman Wahyu; Wardani, I Gusti Agung Ayu Kusuma; Dewi, Ni Kadek Dhea Cipta; Lestari, Ketut Sita Citra (Fakultas Farmasi Universitas Mahasaraswati Denpasar, 2024)
White turmeric is one of the medicinal plants known for its antioxidant properties. This research aims to investigate the antioxidant strength of white turmeric extract (Curcuma zedoaria) by assessing the superoxide dismutase (SOD) activity in an oxidative stress model of white rats (Rattus norvegicus) exposed to cigarette smoke. The study was conducted as an experimental research with a randomized post-test only control group design. Thirty rats were used, divided randomly into six groups: normal control, negative control, positive control, and three treatment groups with extract doses of 100 mg/kgBW, 200 mg/kgBW, and 300 mg/kgBW. The extract was administered daily for 14 days. SOD levels were analyzed using SPSS 26 with the Tukey Post Hoc test. The results showed that the SOD levels in the serum of animals exposed to oxidative stress were 2.71 ng/ml, 2.86 ng/ml, and 3.32 ng/ml at doses of 100 mg/kgBW, 200 mg/kgBW, and 300 mg/kgBW, respectively. The dose of 300 mg/kgBW exhibited the highest antioxidant activity and showed potential to reduce oxidative stress caused by cigarette smoke exposure. This research adds valuable insight into the antioxidant activity of white turmeric ethanol extract and informs the public about its benefits as a natural antioxidant source, particularly in enhancing superoxide dismutase (SOD) activity. It also highlights the potential for white turmeric to be standardized as an herbal product, paving the way for preclinical and clinical trials towards its development as a phytopharmaceutical product.